The structure of decision support systems administrator next information network - Субач, І.Ю.; Хусаінов, П.В.; Міщенко, В.О.; Прусов, Д.Е. (Proceedings of National Aviation University (archive), 2009)
Tasks of execute orderly administrator of special purpose information network are analyzed, and the structure and functions of the system are proved that support taking decisions in real time. Key words: information networks, information services, methods of increasing the efficiency, information evaluation, intellectual data analysis.